Comparing extraction conditions for favorable yield of lutein and zeaxanthin from distiller’s grains - Emily Aicher; Abigail S. Engelberth (Discover Food)
Abstract Sustainable manufacturing practices have become requisite to stretch resources and increase process efficiency. Repurposing waste is a critical strategy to increase sustainability. In bioethanol production, distiller’s grains are a low-value byproduct stream that typically become animal feed. However, corn – and thus distiller’s grains – contains notable levels of lutein and zeaxanthin, carotenoids thought to play a role in maintaining eye health. There is potential to recover additional value from distiller’s grains while repurposing a low-value stream. Conditions to recover lutein and zeaxanthin from either wet distiller’s grains and solubles (WDGS) or dried distiller’s grains and solubles (DDGS) using Soxhlet extraction were investigated and statistically analyzed. Extraction solvent, solid loading, and material type were varied, and the resins were processed using high-performance liquid chromatography (HPLC) to determine the carotenoid content for each condition. The factors causing the greatest changes in yield per gram of sample dry mass were material type (DDGS resulted in a 26% greater yield as compared to WDGS) and solvent (yield with ethanol was 231% greater than with ethyl acetate). Similarly, only material, solvent, and the material × solvent interaction were significant in determining yield (α = 0.05). Solid loading produced only marginal changes in yield per gram of dry mass. Investigating mixing ratios and particle sizes of distiller’s grains, as well as scalable extraction techniques, are the next steps in developing an industrial method of lutein and zeaxanthin recovery. Graphical Abstract